STRATEGI KOMUNIKASI KAMPANYE PRODUK SOSIAL VALUE DAN PRACTICES TENTANG ASI EKSKLUSIF TERHADAP TARGET MARKET PEKERJA - indria flo werina (Jurnal Ranah Komunikasi, 2017)
The social product of Exclusive ASI in Social Marketing is value and practices on Exclusive Breast Milk. ASI is only owned by the mother for her baby. Lactation Center Indonesia sebgai one of the organizers of breast milk campaign in Indonesia, continue to conduct exclusive breastmilk pemasyarakatan. This study aims to describe the communication strategy of Exclusive Breastfeeding campaign by the Lactation Center of Indonesia in an effort to socialize and improve the value and practices of ASI as a social product to the target market workers. Various communication strategies are carried out, among others, by communicator strategy, audience strategy, message strategy, channel choice strategy, and cultural contex strategy. SLI in socializing exclusive breastfeeding chooses personal / group communication channels by way of counseling and lecture / seminar training, besides mass communication channel utilizing broadcast media in reaching a wider audience, also print media and internet. Counseling training participants are open to anyone, mothers, health workers, hospitals / birthplaces and all those concerned about exclusive breastfeeding. In addition to the strategy of seminars / lectures, invited participants from government representatives, parliament, religious leaders, adat leaders, community leaders, Posyandu cadres, PKK and others are all expected to do two step flow communication to the community, this is considered influential as a decision maker or opinion leader. In addition, socialization is done through audio visual mass media, print media and internet as an effort to reach wide target market.